2015
DOI: 10.1007/s12035-015-9361-5
|View full text |Cite
|
Sign up to set email alerts
|

ALCAR Exerts Neuroprotective and Pro-Neurogenic Effects by Inhibition of Glial Activation and Oxidative Stress via Activation of the Wnt/β-Catenin Signaling in Parkinsonian Rats

Abstract: Oxidative stress and neuroinflammation are known causative factors in progressive degeneration of dopaminergic (DAergic) neurons in Parkinson's disease (PD). Neural stem cells (NSCs) contribute in maintaining brain plasticity; therefore, survival of NSCs and neuroblasts during neurodegenerative process becomes important in replenishing the pool of mature neuronal population. Acetyl-L-carnitine (ALCAR), present in almost all body cells, increases endogenous antioxidants and regulates bioenergetics. Currently, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 58 publications
1
29
0
Order By: Relevance
“…Corroborating our earlier findings, a number of recent studies have highlighted the critical importance of WβC crosstalk with survival and inflammatory pathways in inciting neurogenesis and neurorepair Kalamakis et al, 2019;Kase, Otsu, Shimazaki, & Okano, 2019;Mishra et al, 2019;Morrow & Moore, 2019;Ray et al, 2018;Singh, Mishra, Bharti, et al, 2018b;Singh, Mishra, Mohanbhai, et al, 2018a;Singh, Mishra, & Shukla, 2016).…”
Section: Introductionsupporting
confidence: 85%
“…Corroborating our earlier findings, a number of recent studies have highlighted the critical importance of WβC crosstalk with survival and inflammatory pathways in inciting neurogenesis and neurorepair Kalamakis et al, 2019;Kase, Otsu, Shimazaki, & Okano, 2019;Mishra et al, 2019;Morrow & Moore, 2019;Ray et al, 2018;Singh, Mishra, Bharti, et al, 2018b;Singh, Mishra, Mohanbhai, et al, 2018a;Singh, Mishra, & Shukla, 2016).…”
Section: Introductionsupporting
confidence: 85%
“…3), known as the Ames ALA and ALCAR mixture (AAM), the animals' learning improved and decay of brain mitochondria associated with aging was delayed [Liu et al, 2002a,b;Shenk et al, 2009]. Results from extensive studies by Singh et al [2015] using the 6-OHDA rat model of PD-like phenotype concluded that ALCAR's neuroprotective effects are mediated via activation of the Wnt/b-catenin pathway-suggesting its therapeutic use to treat neurodegenerative diseases by enhancing regenerative capacity [Singh et al, 2015]. In ApoE4 transgenic mice, a model of AD [Laurijssens et al, 2013], AAM enhanced cognitive ability and substantially decreased temporal memory loss [Shenk et al, 2009;Ames, 2010].…”
Section: Parkinson Diseasementioning
confidence: 99%
“…SCFA HDACi have a profound influence on microglial homeostasis [Erny et al, 2015]. Microglia are implicated in several pathways of importance in neurodegenerative disorders, including AD and PD [Asai et al, 2015;Boison and Aronica, 2015;Chung et al, 2015;Jyothi et al, 2015;Li et al, 2015;Singh et al, 2015;Br€ uck et al, 2016;Choong et al, 2016;Olson and Gendelman, 2016;Villegas-Llerena et al, 2016]. They constitute the primary active immune defense in the central nervous system and are constantly scavenging for plaques, damaged neurons, and infectious agents [Estes and McAllister, 2015;Mhatre et al, 2015;Matt and Johnson, 2016].…”
Section: Apoptotic Priming In Mitochondriamentioning
confidence: 99%
See 1 more Smart Citation
“…p-GSK3β (Ser9)/total GSK3β protein were significantly decreased, while total GSK3β was increased compared with the normal control ( Figures 4C,D ). β-catenin is a direct substrate of GSK-3β and an intermediate effector of the canonical Wnt signaling pathway (Yost et al, 1996; Singh et al, 2016). GSK-3 activity is also regulated by a wide variety of kinases and systems including the Wnt pathway, Akt, protein kinase A (PKA), protein kinase C (PKC), and MAP kinases (Cross et al, 1995; Chiu and Chuang, 2010).…”
Section: Resultsmentioning
confidence: 99%